Evaluation of galectin-1 and galectin-3 as prospective biomarkers in keratoconus. Issue 5 (8th February 2018) - Andrade, Frans Eberth Costa; Covre, Joyce Luciana; Ramos, Lisandra; Hazarbassanov, Rossen Mihaylov; Santos, Myrna Serapião dos; Campos, Mauro; Gomes, José Álvaro Pereira; Gil, Cristiane Damas
Abstract : Aims: To evaluate the expression of β-galactoside-binding proteins galectin (Gal)-1 and Gal-3 in patients with keratoconus (KC) and postcorneal collagen cross-linking (CXL) treatment in vitro. Methods: Tear fluid, cornea samples and conjunctival impression cytology specimens from control and KC patients were used to evaluate Gal-1 and Gal-3 expressions. Primary keratocytes were isolated by collagenase digestion from surgically removed corneas of five normal or KC human corneal buttons and cultured in Dulbecco's modified eagle medium/Ham's F12 medium supplemented with 2% fetal bovine serum. These cells were evaluated under two experimental conditions: control and submitted to the application of ultraviolet A light and riboflavin 0.1% (CXL) for 30 min. Results: Patients with KC displayed increased levels of Gal-1 and Gal-3 in conjunctival epithelial cells compared with control. Furthermore, KC corneas were associated with intense expression of Gal-1 in the stroma, released by keratocytes. Ultrastructural analysis of keratocytes showed a marked increase of endogenous Gal-3 levels, but not Gal-1, in KC. In vitro, CXL induced significant release of Gal-1 in keratocyte supernatants (116±18 ng/mL, P<0.05) and decreased inflammatory biomarkers as interleukin (IL)-6, IL-8, matrix metalloproteinase (MMP)-2 and MMP-9. Gal-3 levels were not detected in the keratocyte supernatants. Conclusion: Gal-1 and Gal-3 represent new interesting KC biomarkers as revealed by their different expression patterns in KC and control corneal samples. CXL has an immunosuppressive effect on keratocytes by reducing the release of cytokines and MMPs and increased expression of anti-inflammatory protein Gal-1.